Analisis agroeconomico del uso de semilla mejorada de maiz en los Valles Altos de Mexico - Espinosa, A.=700 1 Lopez, M.A.; Tadeo, M.
(En, Es)
ilus., 10 ref.
Keywords: ZEA MAYS; FITOMEJORAMIENTO; HIBRIDOS; SEMILLAS; PRODUCCION; ANALISIS ECONOMICO; COSTA RICA